Diagnostic Performance of Breast-Specific Gamma Imaging (BSGI) for Breast Cancer: Usefulness of Dual-Phase Imaging with (99m)Tc-sestamibi - Park, Ji Sun (Springer-Verlag, 2012)
PURPOSE: The aim of this study was to investigate the usefulness of breast-specific gamma imaging (BSGI) with dual-phase imaging for increasing diagnostic performance and interpreter confidence. METHODS: We studied 76 consecutive patients (mean age: 49.3 years, range: 33–61 years) who received 925 MBq (25 mCi) (99m)Tc-sestamibi intravenously. Craniocaudal and mediolateral oblique planar images were acquired for all patients. Delayed images were obtained from all patients 1 h after tracer injection, except for patients with no definite abnormal uptake. All images were classified into four categories: group 1 (definite negative) = no definite abnormal uptake; group 2 (possible negative) = symmetrically diffuse and amorphous uptake; group 3 (possible positive) = asymmetrically mild and nodular uptake; group 4 (definite positive) = asymmetrically intense and nodular uptake. To evaluate diagnostic performance, the BSGI studies were classified as positive (group 3 or 4) or negative (group 1 or 2) for malignancy according to a visual analysis. The final diagnoses were derived from histopathological confirmation and/or imaging follow-up after at least 6 months (range: 6–14 months) by both ultrasonography and mammography. RESULTS: The patients’ ages ranged from 33 to 61 years, with an average of 49.3 years. Thirteen patients were diagnosed with malignancy, and 63 patients were diagnosed as negative for malignancy. Using early images, 43 patients were classified as group 1, 12 as group 2, 10 as group 3 and 11 as group 4. Based on early images, the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy of BSGI were 77 %, 83 %, 48 %, 95 % and 82 %, respectively. Dual-phase BSGI had a sensitivity, specificity, PPV, NPV and accuracy of 69 %, 95 %, 75 %, 94 % and 91 %, respectively. The BSGI specificity was significantly higher with dual-phase imaging than with single-phase imaging (p = 0.0078), but the sensitivity did not differ significantly (p = 1.0). Based on dual-phase imaging, the sensitivity, specificity, positive predictive value, negative predictive value and accuracy of BSGI for the evaluation of US BI-RADS 4 lesions were 60 %, 86 %, 67 %, 83 % and 78 %, respectively. CONCLUSION: Dual-phase imaging in BSGI showed good diagnostic performance and would be useful for increasing interpreter diagnostic confidence, with higher specificity, positive predictive value and accuracy for breast cancer screening as well as the differential diagnosis of breast disease compared with single-phase imaging.